2021
DOI: 10.1186/s12906-021-03422-y
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical characterization, cytotoxic effect and toxicity evaluation of nanostructured lipid carrier loaded with eucalyptol

Abstract: Background Eucalyptol is an active compound of eucalyptus essential oil and was reported to have many medical attributes including cytotoxic effect on breast cancer cells. However, it has low solubility in aqueous solutions which limits its bioavailability and cytotoxic efficiency. In this study, nanostructured lipid carrier loaded with eucalyptol (NLC-Eu) was formulated and characterized and the cytotoxic effect of NLC-Eu towards breast cancer cell lines was determined. In addition, its toxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 53 publications
(62 reference statements)
1
10
0
Order By: Relevance
“…According to Caldas et al [ 101 ] and Izham et al [ 102 ], 1,8-cineole, the major component of the present sample, showed no indication of toxicity in tests performed with mice. Izham et al [ 102 ] also highlighted that 1,8-cineole had a cytotoxic effect against breast cancer cells without harming the health of the mice subjected to the test.…”
Section: Resultsmentioning
confidence: 44%
See 1 more Smart Citation
“…According to Caldas et al [ 101 ] and Izham et al [ 102 ], 1,8-cineole, the major component of the present sample, showed no indication of toxicity in tests performed with mice. Izham et al [ 102 ] also highlighted that 1,8-cineole had a cytotoxic effect against breast cancer cells without harming the health of the mice subjected to the test.…”
Section: Resultsmentioning
confidence: 44%
“…According to Caldas et al [ 101 ] and Izham et al [ 102 ], 1,8-cineole, the major component of the present sample, showed no indication of toxicity in tests performed with mice. Izham et al [ 102 ] also highlighted that 1,8-cineole had a cytotoxic effect against breast cancer cells without harming the health of the mice subjected to the test. Elmhalli et al [ 103 ] showed that the EOs of Salvadora persica and Rosmarinus officinalis , which contain 1,8-cineole as a major constituent, have moderate toxicity against nymphs of Ixodes ricinus.…”
Section: Resultsmentioning
confidence: 44%
“…Accumulating evidence suggests that the lipophilicity of EOs is suitable for the encapsulation in NLCs which can enhance their therapeutic efficiency by improving stability, bioavailability, and controlled release (Katopodi & Detsi, 2021). Izham et al (2021) (Nordin et al, 2019). In a subsequent study, the same group further revealed the mechanisms of NLC-citral in a 4T1 mice BC model.…”
Section: Eos In Nanostructured Lipid Carriermentioning
confidence: 97%
“…Most of the recent studies on NLCs are based on their application as drug delivery systems (DDSs) for various functions, such as cancer therapy, brain targeting, and antioxidant and anti-inflammatory activities. , Moreover, several researchers have reported the potency of NLC in different administration routes such as skin, oral, parenteral, and intramuscular routes . NLCs have also been reported to exhibit advantages in some nucleic acid-based products such as siRNA from a collagen scaffold as a wound healing material and RNA-based vaccines. , These reports have revealed numerous promising applications of NLCs.…”
Section: Introductionmentioning
confidence: 99%